Getting Gamers : The psychology of video games and their impact on the people who play them - Madigan, Jamie, ....- (Maryland : Rowman & Littlefield, 2016)
Video games are big business. They can be addicting. They are available almost anywhere you go and are appealing to people of all ages. They can eat up our time, cost us money, even kill our relationships. But it's not all bad! This book will show that rather than being a waste of time, video games can help us develop skills, make friends, succeed at work, form good habits, and be happy. Taking the time to learn what's happening in our heads as we play and shop allows us to approach games and gaming communities on our own terms and get more out of them. With sales in the tens of billions of dollars each year, just about everybody is playing some kind of video game whether it's on a console, a computer, a web browser, or a phone. Much of the medium's success is built on careful (though sometimes unwitting) adherence to basic principles of psychology.
Keywords: psychologie; video games